Effect of EMIMTf2N Ionic Liquid on Ionic Liquid-polymeric Membrane (ILPM) for CO2/CH4 Separation - Mannan, H.A. (Elsevier Ltd, 2016)
This paper presented the findings of polyethersulfone / EMIMTf2N blending on morphology and CO2/CH4 separation performance of polyethersulfone membrane. Varying concentration of ionic liquid were incorporated in the dope solution and flat sheet dense membranes were casted by dry phase inversion method. The morphology of the membranes was observed by Field Emission Scanning Electron Microscope (FESEM). The gas permeation experiments were run at room temperature and 2 bar pressure. The membranes showed a dense structure with no pore formation indicating the compatibility of polymer and ionic liquid. CO2 Gas permeability of synthesized polymer/IL membrane was significantly increased by blending ionic liquid in polymer matrix due to high solubility of CO2 in EMIMTf2N ionic liquid. These membranes can be considered as a potential material for bulk removal of CO2 from flue gases and natural gas. Â© 2016 Published by Elsevier Ltd.